AKIBAT HUKUM DARI AKTA JUAL BELI TANAH DIHADAPAN PPAT YANG DIBUAT TIDAK SESUAI DENGAN PROSEDUR PEMBUATAN AKTA PPAT - Istanti Istanti; Akhmad Khisni (Jurnal Akta, 2017)
This research aims to know and analyse which kind of drawing up the land buying-selling certificate categorized as appropriate or not appropriate with the procedures of drawing up a deed by the land certificate issuing officers, and what the legal effect of this procedural distortions is, as stated above.Sociological-empirical research methode which is characterized as descriptive analytic research is applied in this research. Morover, the approach methode applied in this research is empirical juridical qualitative approach with a specification on a prescriptive research. The primary data sources are direct interviews, whereas the secundary data sources are data taken from the primary, secondary and tertiary data. The data collecting is executed by making use of literary studies, interviews and qualitative data analysis.The research findings analyse the buying-selling deed processed in front of the land certificate issuing officers, but which is not executed appropriately in the right procedures. This unprocedural process of drawing up the land deed related to the land buying-selling certificate, is caused by certain situations and conditions of the buying-selling rights executed in front of the officers which are compulsory. Officers are willing to ignore the procedures of drawing a buying-selling certificate as ordered in Government Order No. 37 / 1998 regarding Orders on Officers of Land Certificate Issuing Officer, and Government Order No. 24 / 1997 regarding Land Registration and its executional procedures.Negative effects of the actions done by the land certificate issuing officers who ignore the real procedures, are that, firstly,  the deed can be degraded, and secondly, the officers can be punished to be guilty as a result of their incorrect actions.Keywords : legal effects, deed drawn up by the land certificate issuing officer, buying-selling, procedures.